Application of Sinusoidal Phase Modulation Technique for Infrared Spectrum Measurement by Fourier Transform Method - Doan, Giang; Nguyen, Van Vinh; Nguyen, Thi Phuong Mai; Vu, Thanh Tung (Old Journal, 2017)
The Fourier Transform Infrared (FTIR) spectrometer is widely utilized for the detection and identification of gas in laboratories and open environments. The measurement sensitivity and range of the spectrometry are limited due to the strength of the absorption or emission signals. This study proposes the use of the sinusoidal phase modulation technique to improve the signal to noise ratio (SNR) of the detected signal of an FTIR spectrometer. In this technique, a sinusoidal signal is applied to a voice coil to create movement of a mirror. Hence, the intensity of the interference signal is a series of harmonics. A synchronous detection (lock-in amplifier) is then utilized to detect and amplify only one suitable harmonic and removed all other harmonics and noise. Therefore, the SNR of the harmonic is improved significantly. In this paper, a weak infrared emission from a commercial heat-lamp is detected successfully using the proposed system.